iSCAN: An RT-LAMP-coupled CRISPR-Cas12 module for rapid, sensitive detection of SARS-CoV-2 - Ali, Zahir; Aman, Rashid; Mahas, Ahmed; Rao, Gundra Sivakrishna; Tehseen, Muhammad; Marsic, Tin; Salunke, Rahul; Subudhi, Amit K.; Hala, Sharif M.; Hamdan, Samir M.; Pain, Arnab; Alofi, Fadwa S.; et al. (Virus research, 2020)
•RT-LAMP coupled with CRISPR-Cas12 provides a sensitive and specific virus detection platform.•iSCAN sensitivity and specificity are comparable with RT-qPCR.•iSCAN is a 1 h detection module that can help in testing in low resource areas.•iSCAN can be developed as a one-pot assay.•iSCAN reagents can be produced locally and deployed for SARS-CoV2 detection. The COVID-19 pandemic caused by SARS-CoV-2 affects all aspects of human life. Detection platforms that are efficient, rapid, accurate, specific, sensitive, and user friendly are urgently needed to manage and control the spread of SARS-CoV-2. RT-qPCR based methods are the gold standard for SARS-CoV-2 detection. However, these methods require trained personnel, sophisticated infrastructure, and a long turnaround time, thereby limiting their usefulness. Reverse transcription-loop-mediated isothermal amplification (RT-LAMP), a one-step nucleic acid amplification method conducted at a single temperature, has been used for colorimetric virus detection. CRISPR-Cas12 and CRISPR-Cas13 systems, which possess collateral activity against ssDNA and RNA, respectively, have also been harnessed for virus detection. Here, we built an efficient, rapid, specific, sensitive, user-friendly SARS-CoV-2 detection module that combines the robust virus amplification of RT-LAMP with the specific detection ability of SARS-CoV-2 by CRISPR-Cas12. Furthermore, we combined the RT-LAMP-CRISPR-Cas12 module with lateral flow cells to enable highly efficient point-of-care SARS-CoV-2 detection. Our iSCAN SARS-CoV-2 detection module, which exhibits the critical features of a robust molecular diagnostic device, should facilitate the effective management and control of COVID-19.